MARINE ZOOPLANKTON IN THE WATERS OF SOUTH SAKHALIN AND THE SOUTHERN KURILE ISLANDS - Brodskii,K. A. (1967)
Data processing of plankton samples obtained in Far Eastern Seas is discussed and analyzed. A special Kurile-Sakhalin expedition was organized during 1947-1949 with a view to determining the various plankton species and their distribution in the Bering, Okhotsk and Japan Seas, including the adjacent region of the North Pacific Ocean. This study included the investigation of horizontal and vertical water motions, i.e. the upwelling, the warm and cold currents, which affect the distribution of cryoand thermophilic species of plankton. Further, the distribution of fishes feeding on the plankton was studied, because often the schools of fishes help detect the presence, distribution, and quantity of various plankton species in a given area. (Author) Zooplankton Morskikh vod Yuzhnogo Sakhalina i Yuzhnykh Kurilskikh Ostrovov, trans. of Issledovaniya Fauny Morei (USSR) n6 p5-46 1959.